Diet-induced oxalate nephropathy. Issue 9 (16th September 2019) - Clark, Barbara; Baqdunes, Mohammad Wisam; Kunkel, Gregory M
Abstract : Oxalate nephropathy is a rare condition and may be overlooked due to lack of recognition and understanding of triggers. An 81-year-old man was sent to nephrologist because of significantly increased creatinine (1.5–1.9 mg/dL) noted for 3 months. He had well-controlled diabetes but no history of kidney disease. He had no chronic diarrhoea or intestinal surgery. He was a health-minded individual who had read extensively about benefit of antioxidants. Initial work-up was unrevealing. Within a few weeks after first visit, he developed acute symptomatic worsening kidney injury with nausea, vomiting and creatinine up to 6.8 mg/dL. Repeat examination of the urine sediment revealed casts containing calcium oxalate crystals. A deeper dietary history revealed widespread oxalate precursor consumption. A kidney biopsy confirmed oxalate nephropathy. Restriction of oxalate consumption combined with adequate hydration, oral calcium acetate resulted in partial renal recovery without need for haemodialysis.